Formation of ophiolite-bearing tectono-sedimentary mélanges in accretionary wedges by gravity driven submarine erosion: Insights from analogue models and case studies. (October 2016) - Malavieille, Jacques; Molli, Giancarlo; Genti, Manon; Dominguez, Stephane; Beyssac, Olivier; Taboada, Alfredo; Vitale-Brovarone, Alberto; Lu, Chia-Yu; Chen, Chih-Tung
Abstract: Orogenic wedges locally present chaotic tectonostratigraphic units that contain exotic blocks of various size, origin, age and lithology, embedded in a sedimentary matrix. The occurrence of ophiolitic blocks, sometimes huge, in such "mélanges" raises questions on (i) the mechanisms responsible for the incorporation of oceanic basement rocks into an accretionary wedge and (ii) the mechanisms allowing exhumation and redeposition of these exotic elements in "mélanges" during wedge growth. To address these questions, we present the results of a series of analogue experiments performed to characterize the processes and parameters responsible for accretion, exhumation and tectonosedimentary reworking of oceanic basement lithospheric fragments in an accretionary wedge. The experimental setup is designed to simulate the interaction between tectonics, erosion and sedimentation. Different configurations are applied to study the impact of various parameters, such as irregular oceanic floor due to structural inheritance, or the presence of layers with contrasted rheology that can affect deformation partitioning in the wedge (frontal accretion vs basal accretion) influencing its growth. Image correlation technique allows extracting instantaneous velocity field, and tracking of passive particles. By retrieving the particle paths determined from models, the pressure-temperature path of mélange units or elementary blocks can be discussed. The experimental results are then compared with observations from ophiolite-bearing mélanges in Taiwan (Lichi and Kenting mélanges) and Raman spectroscopy of carbonaceous material (RSCM) Thermometry data on rocks from the northern Apennines (Casanova mélange). A geological scenario is proposed following basic observations. The tectonic evolution of the retroside of doubly vergent accretionary wedges is mainly controlled by backthrusting and backfolding. The retro wedge is characterized by steep slopes that are prone to gravitational instabilities. It triggers submarine landslides inducing huge mass transfers. This erosion combined with backthrusting could favour exhumation of the ophiolitic fragments formerly accreted at the base of the wedge along the rough seafloor-sediments interface. Such an exhumed material can be reworked and deposited as debris- flows in proximal basins located at the foot of the retrowedge slope forming a tectono-sedimentary mélange. These syntectonic basins are continuously deformed and involved in prograding backthrusting-induced deformation.